C'est quoi la violence symbolique. #sociologie #bourdieu #sociologie #politique - Cyril CHEVROT (2021)
Résumé du concept de violence symbolique chez Bourdieu et en particulier dans son livre Domination masculine.
Keywords: approches et analyses; cours; discipline; patriarcat; pol5480; premier cycle; ressource en ligne; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences

The Darkest Hue (Instagram, 2021)
"Jeymes Samuel isn’t much more imaginative than white Hollywood writers and directors. He can’t imagine Stagecoach Mary looking how she did- a beautiful fat, tall, dark-skinned Black woman- and being desired. His casting choices may reflect his *gendered* colorist biases. He hand-picked dark-skinned, monoracial Black actors to play the big, strong, and tough cowboys, despite most of the real-life male characters being fair-complected and mixed-raced. The first person he chose to be Stagecoach Mary was Erykah Badu, a light-brown skinned, thin, and green-eyed Black woman in his 2013 short film They Die by Dawn. He recently chose Zazie Beatz, a light-skinned biracial actress, to play Stagecoach Mary. This infographic essay explores what could have informed these decisions. Light skinned and biracial actresses also have a responsibility to turn down these roles (see slide 9). Don't forget to support me (last slide) if you're able to! #colorism #stagecoachmary #zaziebeetz #thehardertheyfall #jeymesamuel #explorepage #explorepage"
Keywords: 2000 à aujourd'hui; approches et analyses; colorisme; corps; cours; fem3300; intersectionnalité; militance; premier cycle; périodes historiques; racisme; ressource en ligne; sexisme; systèmes d'oppressions; thématiques; violences

The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences

AfroTrans : perspectives, entretiens, poésie, fiction - Danjé, Michaëla; Cxsper, Blxck; Brisac, Michaël; Bémé, Hélène; Descieux, Kellysha; Fénwar, Véli; Gabriel, Joao; Kounkou, Sofiane-Akim; Kuchenga; Lari, Sika; Louïz; Mon-Ink, D.; et al. (Cases Rebelles Editions, 2021)
« Au croisement étoilé de la négritude et de la transidentité, l’accidentelle et lumineuse poésie de nos vies lancée au monde. » Dans cet ouvrage collectif, la parole est donnée exclusivement à des personnes trans noires, vivant en France pour la grande majorité. Ce recueil coordonné par Michaëla Danjé, femme trans membre et co-fondatrice de Cases Rebelles, contient des essais, de la fiction, de la poésie, des interviews, etc. Ce livre est constitué d’une multiplicité de voix, de perspectives et d’expériences diverses. Différentes générations sont également représentées. AfroTrans est beau, complexe, riche de lumière, d’amour et de force !
Keywords: anthologie; approches et analyses; corps; cours; discours dominant; fem3100; identités LGBTQIA2+; outils; ouvrages de références; personnes trans*; premier cycle; racisme; sexisme; systèmes d'oppressions; thématiques; violences

Beurettes : un fantasme français - Diffalah, Sarah; Tenfiche, Salima (Éditions du Seuil, 2021)
"Bimbo orientale habituée des bars à chichas ; femme voilée sage et soumise qui rêve de vacances à Dubaï ; objet sexuel des pires dépravations sur les sites pornos ; «bourgeoise» ambitieuse haut perchée sur ses Louboutin ; ou jeune actrice tchatcheuse qui a gardé l'accent de la cité : les femmes françaises issues de l'immigration maghrébine ne semblent exister dans l'espace médiatique qu'au gré des stéréotypes sans cesse renouvelés de la «beurette». Refusant de se plier à ces préjugés sexistes et racistes, deux d'entre elles sont allées en interviewer d'autres pour explorer les coulisses et les non-dits de cette appellation qu'elles rejettent. Brisant les idées reçues, les autrices révèlent que ces femmes demeurent prisonnières d'un héritage colonial qui continue d'agir. Leur corps est sans cesse au coeur de polémiques qui divisent dans leurs propres rangs musulmans, féministes, associations de femmes « racisées », autant que militant.e.s de gauche ou antiracistes. Une enquête pleine d'empathie qui offre une galerie de portraits, plurielle, pour mieux connaître les «rebeues», loin des caricatures."--Quatrième de couverture.
Keywords: approches et analyses; corps; cours; europe; fem3100; france; premier cycle; racisme; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences

Feu!: abécédaire des féminismes présents - Dorlin, Elsa (Libertalia, 2021)
Plutôt que de réduire le féminisme à des revendications faites à l’État, au patron, au chef ou à papa, pour plus de lois, plus de “sécurité”, à n’être que le porte-drapeau ou le cache-misère du capitalisme, de tel ou tel gouvernement nationaliste, ces histoires des féminismes présents rappellent et font résonner ensemble nos vies féministes. Ce livre fonctionne comme un abécédaire, un manuel, une boîte à outils, un dictionnaire amoureux, dans lequel échanger des idées, affûter des armes, écouter des voix, partager des expériences et des pratiques, vibrer pour des luttes présentes. Il s’adresse à tous·tes : il contient à la fois des ressources et foisonne de références utiles, de notions, mais il est fabriqué par des plumes et des voix, des points de vue situés sur des retours d’expériences collectives, des itinéraires politiques et intimes, des réflexions et des rétrospections sur des parcours, des engagements, des révoltes et des espoirs. En pluralisant les styles, en se situant à la fois du côté de la théorie et de la pratique, de la création, des écritures au “nous” et au “je”, il témoigne de la force d’une approche féministe de l’histoire intellectuelle et politique. Il est dédié à toutes les résistantes anonymes au quotidien des violences les plus crasses, à celles qui embrasent les tribunaux, cassent des genoux et brisent les vitrines, à celles qui inventent mille tactiques imperceptibles pour survivre et se mettre à l’abri, à la mémoire de celles dont les noms recouvrent les murs de nos villes la nuit, à la puissance des collectifs qui se font, à ceux qui se sont défaits, qui se sont (re)constitués ailleurs ou autrement, à ce qui nous lie.
Keywords: afro-féminisme; approches et analyses; corps; cours; droits des femmes*; fem3100; féminisme décolonial; féminismes noirs; genre; identités LGBTQIA2+; intersectionnalité; inégalités; outils; ouvrages de références; premier cycle; queer; racisme; sex2283; sexisme; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; écoféminisme

Hidden in plain sight: Uncovering the emotional labor of Black women students at historically White colleges and universities. - Kelly, Bridget T.; Gardner, Paige J.; Stone, Joakina; Hixson, Ashley; Dissassa, Di-Tu (Journal of Diversity in Higher Education, 2021)
We utilized the emotional labor triangle to understand how 16 Black women students who attended Historically white colleges and universities (HWCUs) navigated gendered-racialized oppressive environments that mattered to their academic success. This study contributes to a gap in the literature, as much of the research focused on students of color without disaggregating for gender or other social identities. In addition, the literature is scant on experiences of Black women students use of emotional labor. Emotional labor has largely been studied from a management perspective. Through qualitative semi-structured interviews, we examined the emotional labor Black women expended while pursuing their undergraduate degree. We employed a qualitative, intersectional, methodological approach to foreground historically marginalized voices and situated the study in the hypervisibility Black women participants described feeling as space invaders on their historically White undergraduate campus and at the same time the invisibleness of their voice and masking of their feelings as they encountered gendered racism. Further, we emphasized the emotional toll and stress that may occur for Black women when they do not utilize engaged coping mechanisms while expending their emotional labor. The study holds implications for educators to address emotional labor inequities within HWCUs. (PsycInfo Database Record (c) 2021 APA, all rights reserved) © 2019 National Association of Diversity Officers in Higher Education
Keywords: amériques; approches et analyses; care; colère; femmes universitaires noires*; intersectionnalité; projet charge mentale; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail émotionnel; violences; états-unis

Les mots de trop - Les mots de trop (2021)
Les mots de trop est un outil de lutte et de sensibilisation à destination de tous·tes les étudiant·es des milieux de la culture.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; arts; belgique; capacitisme; discipline; france; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; suisse; système colonial; systèmes d'oppressions; thématiques; témoignages; violences

Before the “Ecologically Noble Savage”: Gendered representations of Amazonia in the global media in the 1970s - Sarzynski, Sarah (Latin American Perspectives, 2021)
An analysis of media representations of the Amazon and indigenous peoples reveals how media producers and filmmakers foregrounded discourses naturalizing gendered and racialized differences that distinguished the Amazon from the West in the 1970s, a decade during which the Brazilian military dictatorship promoted development projects in Amazonia. These representations often sexualized indigenous peoples and the Amazon itself, portraying them as primitive, cannibal savages, animals or part of nature, or victims of exploitation. The “Othering” of the Amazon and Amazonians was further elaborated through a discourse of binary oppositions that portrayed Western white men as explorers and exploiters who dominated the screen, scripts, studies, and development projects even if they were doomed to fail. By relying on a symbolic system of difference, global media coverage and films about Amazonia in the 1970s were complicit in legitimizing authoritarian decrees promoting large-scale development that depicted indigenous peoples and the environment as obstacles. Un análisis de las representaciones mediáticas de la Amazonía y sus pueblos indígenas revela cómo, en la década de 1970, productores y cineastas mediáticos resaltaron discursos que naturalizaron las diferencias de género y racializadas con las que se distinguían a la Amazonía del Occidente en una época durante la cual la dictadura militar brasileña promovió proyectos de desarrollo en la región. Dichas representaciones a menudo sexualizaban a los pueblos indígenas y a la Amazonía misma, retratándolos como primitivos, caníbales salvajes, animales o elementos naturales, o víctimas de explotación. La “otredad” de la Amazonía y los amazónicos se elaboró a través de un discurso de oposiciones binarias que retrataba a los hombres blancos occidentales como exploradores y explotadores que dominaban la pantalla, los guiones, los estudios y los proyectos de desarrollo, incluso si estos estaban condenados al fracaso. Al confiar en un sistema simbólico de diferencia basado en oposiciones binarias y estereotipos, la cobertura mediática global y las películas sobre la Amazonía en la década de 1970 fungieron como cómplices en la legitimación de los tipos de proyectos y políticas llevados a cabo en la región. © 2021 Latin American Perspectives.
Keywords: amazonie; amériques; approches et analyses; brésil; discipline; domination blanche; domination masculine; histoire; histoire et politique; médias; peuples autochtones; projet charge mentale; racisme; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; violences coloniales; violences racistes; violences sexistes

Dead white men vs. Greta Thunberg: Nationalism, misogyny, and climate change denial in swedish far-right digital eedia - Vowles, Kjell; Hultman, Martin (Australian Feminist Studies, 2021)
In the autumn of 2018 Greta Thunberg started her school strike. Soon she and the Fridays For Future-movement rose to world-fame, stirring a backlash laying bare the intrinsic climate change denial of Swedish far-right digital media. These outlets had previously been almost silent on climate change, but in 2019, four of the ten most read articles on the site Samhällsnytt were about Thunberg, all of them discrediting the movement and spreading doubt about climate science. Using the conceptualisation of industrial/breadwinner masculinities as developed by Hultman and Pulé [2018. Ecological Masculinities: Theoretical Foundations and Practical Guidance. Routledge Studies in Gender and Environments. New York: Routledge], this article analyses what provoked this reaction. It explores how the hostility to Thunberg was constructed in far-right media discourse in the years 2018–2019, when she became a threat to an imagined industrial, homogenic and patriarchal community. Using conspiracy theories and historical tropes of irrational femininity, the far right was trying to protect the usually hidden environmental privileges, related to unequal carbon emissions and resource use, that Thunberg and her movement made visible. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discous dominant; environnement; europe; extrême-droite; histoire et politique; misogynie; médias; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; suède; systèmes d'oppressions; thématiques; violences

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences

Psychologie du sexisme : des stéréotypes de genre au harcèlement sexuel - Faniko, Klea; Dardenne, Benoit (Collection Ouvertures psychologiques. LMD, 2021)
"Depuis plusieurs années et sous l'impulsion de mouvements sociaux comme #MeToo, de nombreuses affaires de violences sexistes et sexuelles, impliquant des personnalités publiques ou des institutions connues, éclatent au grand jour dans les médias. Ces différents témoignages de femmes mettent en lumière l'ampleur des violences sexistes et sexuelles dans le monde. Comment expliquer une telle prévalence? Quels processus psychologiques peuvent conduire à l'apparition de stéréotypes, de préjugés et de discriminations sexistes? L'objectif de cet ouvrage, rassemblant 45 chercheurs francophones, est de contribuer à la compréhension des conséquences des discriminations sexistes, mais surtout d'aider à décrypter leurs mécanismes. Le phénomène s'avère complexe et très souvent subtil, prenant diverses formes et étant profondément inscrit dans les rouages de la société et des rapports humains. En plus des analyses présentées dans l'ouvrage, différentes pistes d'action sont proposées pour les entreprises et les institutions souhaitant promouvoir un environnement de travail inclusif."--Quatrième de couverture.
Keywords: EDI; approches et analyses; cours; discipline; discours dominant; discriminations; harcèlement sexuel; outils; outils didactiques; premier cycle; psy4910; psychologie; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences